Comparing the Effects of a Herbal Drug based on Echium Amoenum With Fluvoxamine in the Treatment of Adolescents with Obsessive-compulsive Disorder - Noras, Mohamad R.; Soltanifar, Atefeh; Salari, Roshanak; Jarahi, Lida; Abrishami, Maryam Hosseini (Current Drug Discovery Technologies, 2022)
Background: Obsessive-compulsive disorder (OCD) is a severe and debilitating neuropsychiatric condition. Although selective serotonin reuptake inhibitors, tricyclic antidepressants, and cognitive- behavioral therapy are the first-line medication and treatment for OCD, an estimated 30% of patients are treatment-resistant, and complete functional recovery is rare. Natural products as adjuvant or alternative therapies should be examined to find safer and more effective ways to manage OCD. Objectives: To investigate the potential benefits of a combined herbal drug based on Echium amoenum in treating OCD. Methods: Design and Setting: In the psychiatric clinics of Mashhad University of Medical Sciences, 40 patients who met the criteria for the obsessive-compulsive disorder based on DSM-5 were studied in a parallel, double-blind, randomized clinical trial. Intervention: Subjects were randomly assigned to receive Echium amoenum-Melissa officinalis syrup and fluvoxamine or placebo syrup and fluvoxamine for 8 weeks. Outcome Measures: The efficacy of treatment and recurrence of disease were surveyed and compared according to the Yale-Brown Obsessive Compulsive Scale at weeks 0, 4, and 8. Results: Evaluation at the 4th and 8th week showed no significant differences between the two groups (p-value = 0.11, p-value = 0.445, respectively). At the 8th week of treatment, patients in the intervention group showed a remarkable reduction in scores on the Yale-Brown Obsessive-Compulsive Scale questionnaire (p- value= 0.003), and patients in the control group didn't ((p- value= 0.180). This study showed that the E.amoneum-M.officinalis syrup was not significantly more efficacious than the fluvoxamine tablet, but the intervention group showed a significant improving trend (p-value= 0.001). Conclusion: While monotherapy is usually the gold standard methodology, combination or augmentation therapy may also be of merit. Consequently, studies with larger sample sizes and the inclusion of para-clinical assessments such as serologic tests can further shed light on the mechanism of action of the E. amoneum- M. officinalis syrup and deepen our understanding of its effects.
Keywords: persian medicine